2021
DOI: 10.31073/kormovyrobnytstvo202192-09
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the determining the sowing properties of seeds of perennial grasses express method effectiveness in comparison with domestic and international rules

Abstract: Purpose. To theoretically substantiate the methodology for the accelerated determination of the sowing qualities (express method) of seeds of leguminous and cereal grasses, in particular germination capacity, the amount of hard seeds and viability in comparison with the defining those indicators according to the State standard of Ukraine (SStU 4138-2002), international methodology (ISTA – International seed testing association). Methods. Quantitative, laboratory, mathematical-statistical, observation, comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Diseases and pests account for 10-15%, and varieties -15-25%. It is indicated that the "outsized" use of phosphorus and potash fertilisers for three years was more effective than their annual application in a dose of P 60 K 60 and provided an increase in yield in the range of 20-28% (Antoniv et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Diseases and pests account for 10-15%, and varieties -15-25%. It is indicated that the "outsized" use of phosphorus and potash fertilisers for three years was more effective than their annual application in a dose of P 60 K 60 and provided an increase in yield in the range of 20-28% (Antoniv et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%